Assessment of Feed Resources Availability for Livestock in the Semi Arid Region of Andhra Pradesh, India - Reddy, P. Ravi Kanth; Jakkula, Raju; Reddy, A. Nagarjuna; Kumar, D. Srinivasa; Lakshmi, R.K. Sowjanya; Hyder, Iqbal (Indian Journal of Animal Nutrition, 2018)
This study was conducted to assess feed resource availability in two of the 6 agro-climatic zones of Andhra Pradesh i.e., southern zone (Chittoor, Kadapa and Nellore) and scarce rainfall zone (Anantapur and Kurnool) which are relatively deficient in rainfall as compared to the remaining zones. The dry agro climatic zones of Andhra Pradesh were deficient in total dry matter availability of feeds to meet the requirements of livestock and poultry. Furthermore, there was a severe shortage of green forages and concentrates to meet the requirements of milch cattle and poultry. Even though the region was marginally self-sufficient in terms of dry forage availability, the majority of these forages were nutritionally poor cereal straws. Hence, suitable strategies should be developed for the efficient utilization of existing feed and fodder resources to improve animal productivity in region.